Antioxidant activity of hexahydroquinolines - Tarun, Ekaterina I.; Dankova, Anastasiya V.; Pyrko , Anatoly N. (Journal of the Belarusian State University. Ecology, 2019)
Comparative characteristics of the antioxidant properties of five different structures held hexahydroquinolones conducted. The dependence of the fluorescence intensity of fluorescein from the logarithm of the concentration of hexahydroquinolones, of which graphically determined indicators IC50. IC50 values in this series was 0,32–5,5∙10-7 М. Hexahydroquinolones have a high antioxidant activity, restoring the fluorescein fluorescence intensity to 76–94 %. An analysis of the contribution of individual functional groups, such as methoxy groups and carboethoxy groups, as well as their amounts and locations relative to each other during the binding of free radicals is done.
Keywords: antioxidant activity; hexahydroquinolones; fluorescein